DIGITALISASI SISTEM PEMBAYARAN DALAM PERSPEKTIF EKONOMI ISLAM: TINJAUAN SISTEMATIS KEABSAHAN E-WALLET DAN CRYPTOCURRENCY - Narendra Ridha Baihaqi; Herbert Siregar; Muhammad Haikal Ali (Indonesian Scientific Journal of Islamic Finance, 2026)
The rapid development of financial technology has significantly transformed modern payment systems, particularly through the use of digital money such as e-wallets and cryptocurrencies. These innovations offer efficiency, speed, and convenience in transactions; however, they also raise debates regarding their compliance with Islamic economic principles. This study aims to systematically analyze the concept of digital money, its sharia legitimacy, implementation challenges, and development strategies from the perspective of Islamic economics. This research employs a Systematic Literature Review (SLR) method by examining scholarly articles obtained from Google Scholar and Scopus databases. The literature selection process follows the PRISMA framework with clearly defined inclusion and exclusion criteria, resulting in a set of relevant articles analyzed based on five research questions. The findings indicate that e-wallets are generally acceptable within Islamic economics, provided they are supported by clear contractual structures, transparent fee mechanisms, and are free from elements of riba, gharar, and maysir. In contrast, cryptocurrencies remain subject to ongoing debate due to their high price volatility and speculative characteristics, leading many studies to position them more as digital assets rather than legitimate mediums of exchange. The main challenges in implementing sharia-compliant digital money include regulatory limitations, low levels of Islamic financial literacy, and the integration of digital features that may deviate from sharia principles. Therefore, the development of Islamic digital money should be guided by the maqÄá¹£id al-sharÄ«”˜ah framework to ensure justice, asset protection, and social welfare.